Knee Septic Arthritis after Palm Tree Thorn Injury: A Case Report - Ramos, Jorge Teixeira; Barbosa, Nuno; Almeida, João; Karmali, Samir; Guerreiro, Rui; Magalhães, Glória (My University, 2021)
Introduction:A monoarthritic painful knee may have multiple etiologies, of which septic arthritis is commonly considered to be one of the most deleterious pathologies. This type of acute symptom is, in the literature, for some rare cases, related to an inflammatory process secondary to a penetrating plant thorn, which was considered an aseptic process and therefore treated by removing the foreign body. This work reports a recent case falling into that diagnosis, which due to its infrequent nature, could have been misevaluated and consequently mistreated. Case Report: Our goal is to bring to the attention of the orthopedic community that this type of deleterious pathology, which is today uncommon, must never be fully disregarded. We share a case of a 68-year-old male who was admitted 2 days after being injured by a palm tree (Arecaceae) thorn with acute inflammatory signs and effusion in the left knee. Although, ultrasound excluded pathway or intra-articular foreign bodies, in the arthroscopic procedure, a thorn was found and removed. Pantoea agglomerans was identified in the synovial fluid. Conclusion: Following the removal of the foreign body, empirical antibiotic treatment with coverage against Gram-negative pathogens was initiated and later on replaced by appropriate antibiotics, after susceptibility testing is obtained.
Keywords: Knee; palm tree; pantoea agglomerans; septic arthritis; thorn